Peculiarity of hybrid entrepreneurs – revisiting Lazear’s theory of entrepreneurship - Kurczewska, Agnieszka; Mackiewicz, Michał; Doryń, Wirginia; Wawrzyniak, Dorota (Journal of Business Economics and Management, 2020)
The aim of this study is to explore and elaborate the concept of hybrid entrepreneurship, i.e., a simultaneous mix of self-employment (entrepreneurship) and salary employment. Lazear’s theory of entrepreneurship is assessed in terms whether it can explain the phenomenon of being a hybrid entrepreneur. The hypothesis is that the probability of linking a salary job with one’s own business increases with the variety and level of education gained, the broadness of professional and management experience but also the level of entrepreneurial self-efficacy. The hypotheses are tested with multivariate logistic regression, using survey data gathered from 1600 entrepreneurs. In light of the results, Lazear’s theory cannot be unambiguously extended to the case of hybrid entrepreneurs. Although the probability of being a hybrid entrepreneur increases with broader professional and managerial experience, at the same time it diminishes as the level and diversity of education increase. The results suggest that hybrid entrepreneurs are an importantly discrete population and therefore need to be treated separately. The theoretical and practical implications of the results are discussed.